Penerapan Metode Drill Untuk Meningkatkan Pemahaman Qowaid Nahwiyyah Di Madrasah Diniyyah Al- Amiriyyah Blokagung Banyuwangi - M Alaika Nasrullah; Muhammad Irfani; Mahbub Mahbub (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2023)
This article is the result of research that aims to find out how the application of the drill method is used in the process of improving the qowaid nahwiyyah abilities of superior program students at madrasah diniyyah al-amiriyyah, as well as to find out the advantages and disadvantages of its application. This research approach is descriptive qualitative with grounded theory type, which uses three data collection methods, namely interviews, observation and documentation. The results of this study indicate that the implementation of learning by applying the drill method in increasing understanding of qowaid nahwiyyah is in accordance with the theory and achieving maximum results. In the learning process, the teacher goes through the steps of preparation, implementation and evaluation. The drill method in qowaid nahwiyyah learning is very effective, by repeating material it really helps students understand material with different backgrounds, the drill method can make students active in learning and delivering material in short and clear language. In addition, student responses to the application of the drill method were very positive, because there was an interactive dialogue between the teacher and students. In addition to these har, there are also advantages and disadvantages in the implementation of learning using the drill method. The advantages of applying the drill method include: high student interest in learning and enthusiasm in understanding the material, it is easier to find out the problems experienced by students in understanding the material, in a short time gaining mastery of the material according to the target. The disadvantages of the drill method are: students feel bored participating in learning, students feel more pressured because evaluations are often held, students often arrive late so that learning time is delayed and the facilities they have are inadequate.